Phytoremediation: A Sustainable Approach for Reclamation of Heavy Metals Contamination - Pawan Kumar Verma; Priyanka Sharma; Bhawani Singh; Nrip K Pankaj; Rajinder Raina (Mazandaran University of Medical Sciences, 2024)
Background and Objectives: Humanity's gravest issue is environmental pollution, the main source of illness and death in humans and animals. The rapid exploitation of natural resources, urban effluents, and growing industrial waste result from the industrial and technological revolution, resulting in pollution. In the last few decades, the conventional technologies and processes used to remove the contaminants have typically been ineffective, expensive and harmful to the environment.  Methods: The study's available resources were compiled from internationally recognized scientific databases.  Results: The use of phytoremediation for sustainable recovery of areas contaminated with toxic heavy metals has gained higher status since the discovery of hyper-accumulator plants. Numerous species of aquatic plants are effective in removing organic and inorganic pollutants. However, choosing plant species is of primary importance for successful phytoremediation. Other novel approaches, like different bio-absorbents and their modified versions, such as nano-composites and carbonaceous materials, might also be helpful for the sequestration of heavy metals in soil. Conclusion: The microbiological adsorbents and modified agriculture biomass composites effectively render heavy metals inert in soil and water with greater performance, stability, and reusability. The modified composites encapsulated bio-absorbents for cleaning up contaminated water and soil can be a better alternative and must be explored for future use.